Victory Strategy of Cigentur Village Head, Bandung Regency - Kurniabudi, Budi; Suhara, Ero; Rudiansah, Bambang; Rustandi, Arya Saputra; Fadhilah, Ryal Nur; Pahabol, Eliza; Seftiani, Jingga; Merani, Anisa; Mutiara, Davina; Dzakiatunnisa, Wafa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Research explains the village head's winning strategy, with an emphasis on political aspects, campaigns and political communication. The focus includes planning, managing and identifying supports. This strategy is considered important in the context of democracy by the Head of Cigentur Village. This research uses Firmansyah's political marketing theory which includes This product, promotion, price and place. The Cigentur Village Head is known to be close to his village residents through active, friendly relationships, and always listens to input and communicates effectively and actively contributes to the community. The Cigentur Village Head's programs and plans include infrastructure development, building Ragas paud and the Cindikia Bojong Paseh Vocational School foundation, then in his education program he focuses on the problem of stunting by building 8 community posyandu to overcome stunting in his health program. and the regional economic development program includes development with an interest-free money loan program, by minimizing mobile bank loans which can cause misery for the community. One of the campaigns carried out against the Cigentur community was a religious campaign by carrying out terawih at around 39 mosques. This is a form of introduction and friendship with the community. campaign costs reached around 200 million in the first period. The difference in votes obtained by the Cigentur Village Head in the first and second periods was approximately hundreds, while in the third period the difference was approximately thousands of votes. Family background h. Hidayat or the Head of Cigentur Village mostly works as an entrepreneur